BUILDING AND IMPLEMENTING PRICING STRATEGIES BASED ON PREDICTIVE ANALYTICS: INCREASING COMPETITIVENESS - GANUSHCHAK-YEFIMENKO, Lyudmyla (Scientific journal «World of Finance», 2025)
Introduction. In the context of dynamic market changes and the development of new technologies, such as big data and artificial intelligence, companies are forced to find new approaches to the formation of their pricing strategies. One of the most promising tools for optimizing pricing is predictive analytics, which allows you to predict consumer behavior, change in demand, analyze the competitive environment and determine optimal prices for goods or services in different conditions.The purpose of the article is to determine the main directions of building and implementing pricing strategies based on predictive analytics in order to ensure increased competitiveness of business structures.Results. The presented work considers the main features of predictive analytics as the main basis for the formation of modern pricing strategies to ensure competitiveness. The features of building predictive models are also substantiated, which made it possible to propose a methodical approach to the implementation of pricing strategies based on predictive analytics.Conclusions. The implementation of pricing strategies based on predictive analytics is an important step in increasing the competitiveness of enterprises in modern economic conditions. The use of predictive models allows companies to effectively predict changes in demand, analyze the behavior of consumers and competitors, which makes it possible to optimize prices and adapt to a rapidly changing market.